PENGARUH MEKANISME TATA KELOLA PERUSAHAAN TERHADAP AUDIT REPORT LAG DENGAN VARIABEL MODERASI UKURAN PERUSAHAAN (EMITEN BASIC MATERIALS BURSA EFEK INDONESIA PERIODE 2021-2023) - Nurmaulida, Amanda; Mukti, Aloysius Harry; Eprianto, Idel (SINERGI : Jurnal Riset Ilmiah, 2025)
The study aims to test the size of the Board of Commissioners, the size of the Audit Committee, and the number of Audit Committee Meetings on Audit Report Lag with the moderating variable of company size. The study population is all Basic Materials Issuers on the Indonesia Stock Exchange for the 2021-2023 period. The sampling technique used is the purposive sampling method, and 63 issuer samples were obtained. The analysis methods used are descriptive statistical analysis, multiple linear regression analysis, hypothesis testing, and moderation regression analysis. The results of this study indicate that partially the size of the Board of Commissioners has a negative effect on Audit Report Lag, the size of the Audit Committee has a positive effect on Audit Report Lag, and the variable number of Audit Committee meetings has no effect on Audit Report Lag. The results of the study for the moderating variable, namely Company Size, are able to moderate (weaken) the negative effect of the Size of the Board of Commissioners on Audit Report Lag, and Company Size is unable to moderate the Size of the Audit Committee and the Number of Audit Committee Meetings.